2019
DOI: 10.3892/ol.2019.11121
|View full text |Cite
|
Sign up to set email alerts
|

The HPA/SDC1 axis promotes invasion and metastasis of pancreatic cancer cells by activating EMT via FGF2 upregulation

Abstract: Pancreatic cancer is characterized by the absence of early specific clinical symptoms, accompanied with rapid metastasis and invasion. It is one of the most prevalent types of cancer and more importantly, one of the most common types of malignant cancer with the highest mortality rate of all cancer types. The heparanase (HPA)/syndecan-1 (SDC1) axis has been reported to promote tumor growth, invasion, metastasis and angiogenesis in a variety of cancer types; however, studies into the role and mechanism of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…For instance, it impacts on cell differentiation, angiogenesis and inflammatory responses, thus contributing to tumorigenesis [26]. Notably, FGF2 facilitates cell migration and invasion in some cancers like breast, pancreatic and cervical cancers [27][28][29]. In this study, we confirmed the pro-metastasis function of FGF2 in CC.…”
Section: Discussionsupporting
confidence: 76%
“…For instance, it impacts on cell differentiation, angiogenesis and inflammatory responses, thus contributing to tumorigenesis [26]. Notably, FGF2 facilitates cell migration and invasion in some cancers like breast, pancreatic and cervical cancers [27][28][29]. In this study, we confirmed the pro-metastasis function of FGF2 in CC.…”
Section: Discussionsupporting
confidence: 76%
“…We found that the heparanase/syndecan-1 (HPA/SDC1) axis can up-regulate the FGF2 level and increase the expression of downstream palladin by activating the phosphoinositide 3-kinase/Akt (PI3K/Akt) signaling pathway, thereby leading to the activation of EMT. We also reported that EMT promotes the migration and invasion of pancreatic cancer cells [27] .…”
Section: Discussionmentioning
confidence: 73%
“…14,24 For instance, SDC1 was reported to be an oncogene in glioma, renal cell cancer and pancreatic cancer. [25][26][27] However, some studies also showed that SDC1 functioned as a tumor suppressor in colorectal cancer, oral cancer and gallbladder cancer. [28][29][30] These data suggested that SDC1 might exert specific roles in different cancers.…”
Section: Discussionmentioning
confidence: 99%